Gizi, Asuh, Tumbuh! Edukasi Pola Asuh Makan untuk Pencegahan Stunting dan Mendukung Tumbuh Kembang Anak - Pratiwi, Ismayanti; Adeni, Susri; Harahap, Machyudin Agung (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Stunting is a chronic nutritional problem that is still a serious challenge in Indonesia, including in Bogor Regency, with a prevalence that exceeds the threshold set by WHO. Inappropriate eating patterns, including a lack of understanding of nutrition and responsive feeding, are one of the main causes of stunting. This community service activity aims to improve the knowledge and skills of Posyandu cadres regarding eating patterns that support stunting prevention and optimal child growth. The activity was carried out in Cibatok I and II Villages, Cibungbulang District, Bogor Regency. The methods used included interactive lectures, discussions, and simulations that focused on the principles of balanced nutrition, responsive feeding, and communication and emotional practices in feeding. Cadres also showed enthusiasm and readiness to become education agents in their communities. Educating about eating patterns through Posyandu cadres is a strategic and effective approach in supporting stunting prevention efforts at the community level.